Accounting for Financial Reporting in Regional Public Service Agency (BLUD) Health Sector - Arunio Ramadito (Journal of Accounting Auditing and Business, 2022)
This study aims to provide an overview of the financial reporting accounting in the Regional Public Service Agency (BLUD). Units analysis are public services in the health sector, namely Regional General Hospital (RSUD) and the Community Health Center (Puskesmas) work unit. In implementing financial reporting accounting, BLUDs must apply reports following Government Accounting Standards Statement (PSAP) Number 13 of 2015 concerning Presentation of Financial Statements for Public Service Agencies (BLU). This study uses a qualitative method by reviewing several literature studies on financial reporting accounting in the health sector BLUD. The research method using literature review reviews can facilitate research in identifying and analyzing problems and available information regarding financial reporting accounting at the BLUD in the health sector. This article aims to identify BLU financial reporting based on PSAP 13 and its implementation in BLUDs that provide services to the community in the health sector, namely RSUD and Puskesmas. Local governments are expected to improve the accounting quality of BLUD financial reporting by establishing clear regulations and SOPs, increasing the capacity of BLUD human resources, and improving the quality of BLUD infrastructure to support sound financial reporting accounting processes.